Right ventriculo-arterial coupling in pulmonary hypertension: a magnetic resonance study. Issue 3 (13th September 2011) - Sanz, Javier; García-Alvarez, Ana; Fernández-Friera, Leticia; Nair, Ajith; Mirelis, Jesús G; Sawit, Simonette T; Pinney, Sean; Fuster, Valentin
Abstract : Objective: To quantify right ventriculo-arterial coupling in pulmonary hypertension by combining standard right heart catheterisation (RHC) and cardiac magnetic resonance (CMR) and to estimate it non-invasively with CMR alone. Design: Cross-sectional analysis in a retrospective cohort of consecutive patients. Setting: Tertiary care centre. Patients: 139 adults referred for pulmonary hypertension evaluation. Interventions: CMR and RHC within 2 days (n=151 test pairs). Main outcome measures: Right ventriculo-arterial coupling was quantified as the ratio of pulmonary artery (PA) effective elastance (Ea, index of arterial load) to right ventricular maximal end-systolic elastance (Emax, index of contractility). Right ventricular end-systolic volume (ESV) and stroke volume (SV) were obtained from CMR and adjusted to body surface area. RHC provided mean PA pressure (mPAP) as a surrogate of right ventricular end-systolic pressure, pulmonary capillary wedge pressure (PCWP) and pulmonary vascular resistance index (PVRI). Ea was calculated as (mPAP − PCWP)/SV and Emax as mPAP/ESV. Results: Ea increased linearly with advancing severity as defined by PVRI quartiles (0.19, 0.50, 0.93 and 1.63 mm Hg/ml/m 2, respectively; p<0.001 for trend) whereas Emax increased initially and subsequently tended to decrease (0.52, 0.67, 0.54 and 0.56 mm Hg/ml/m 2 ; p=0.7). Ea /Emax was maintained early but increased markedly with severe hypertension (0.35, 0.72, 1.76 and 2.85; p<0.001), indicating uncoupling. Ea /Emax approximated non-invasively with CMR as ESV/SV was 0.75, 1.17, 2.28 and 3.51, respectively (p<0.001). Conclusions: Right ventriculo-arterial coupling in pulmonary hypertension can be studied with standard RHC and CMR. Arterial load increases with disease severity whereas contractility cannot progress in parallel, leading to severe uncoupling.